Rethinking Society for the 21st Century : report of the international panel on social progress. Volume 2, Political regulation, governance, and societal transformations. - International Panel on Social Progress (Cambridge : Cambridge University Press, 2018)
This is the second of three volumes containing a report from the International Panel on Social Progress (IPSP). The IPSP is an independent association of top research scholars with the goal of assessing methods for improving the main institutions of modern societies. Written in accessible language by scholars across the social sciences and humanities, these volumes assess the achievements of world societies in past centuries, the current trends, the dangers that we are now facing, and the possible futures in the twenty-first century. It covers the main socio-economic, political, and cultural dimensions of social progress, global as well as regional issues, and the diversity of challenges and their interplay around the world. This particular volume covers topics such as democracy and the rule of law, violence and wars, international organizations and global governance, and media and communications.
Title from publisher's bibliographic system (viewed on 25 Jul 2018).
Keywords: Social change; Progress; Political science; Civilization -- 21st century